The Representation of Gender Inequality in Mulan (2020) Movie - Auliya Nur Fajrina; Dewi Candraningrum (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
Literary work is one the ways that a person uses to express ideas, thoughts, and feelings in the form of a work that is represented aesthetically. Nowadays, there are many issues regarding gender inequality that occur in society. This is one of the problems for women regarding rights that are not obtained as women. This study discusses the Mulan (2020) movie which was released on 9th March 2020 where the movie shows the reality of life that adheres to a patriarchal ideology in which women are considered weak. This research aims to determine the representation of gender inequality in Mulan (2020) movie which uses descriptive qualitative research method and feminism approach. Gender inequality is shown through 4 indicators, limited opportunities in utilizing resources, limited opportunities to participate in an activity, limited authority in making decisions, and limited recognition in decision making. The representation of gender inequality can be seen through the characters, setting, events, and style. The reason of Niki Caro addressing gender inequality in the Mulan (2020) movie is found in the personal life of the director where the director is an activist for women’s rights.